2021
DOI: 10.1111/tmi.13588
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of hepatitis B vaccination in chronic HCV patients after successful generic direct acting antiviral therapy: significance of isolated hepatitis B core antibodies

Abstract: Objective Previous reports show conflicting results regarding hepatitis B virus (HBV) vaccine efficacy in Hepatitis C virus (HCV) infected individuals and in those with isolated hepatitis B core antibodies (HBcAb). We aimed to evaluate the effectiveness of HBV vaccine and identify possible factors that may contribute to hyporesponsivness in HCV‐treated patients, including those with isolated HBcAb. Methods We conducted a prospective study with 118 enrolled chronic HCV patients who followed a 12‐week regimen of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Another prospective study evaluated the seroconversion of the HBV vaccine in chronic HCV patients who had undergone treatment with DAAs. The study found that hypo-responsiveness to the HBV vaccination is frequent in chronic HCV patients even after achieving sustained virologic response following direct-acting antiviral therapy [13] . The evidence from these studies supports the notion that chronic HCV infection is associated with decreased responsiveness to the HBV vaccine.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Another prospective study evaluated the seroconversion of the HBV vaccine in chronic HCV patients who had undergone treatment with DAAs. The study found that hypo-responsiveness to the HBV vaccination is frequent in chronic HCV patients even after achieving sustained virologic response following direct-acting antiviral therapy [13] . The evidence from these studies supports the notion that chronic HCV infection is associated with decreased responsiveness to the HBV vaccine.…”
Section: Discussionmentioning
confidence: 92%
“…Several risk-factors, such as sex, age, smoking, body mass index (BMI), and HCV infection may impact HBV vaccine immunogenicity [10] , [11] , [12] , [13] . Understanding the factors influencing the vaccine response can help to inform vaccination recommendations and improve vaccination rates.…”
Section: Introductionmentioning
confidence: 99%
“…HBcAb, or hepatitis B core antibodies, are immunoglobulins produced by the body in response to the presence of HBcAg. These antibodies serve as serological markers to indicate previous or ongoing HBV infection, as they can be detected during both acute and chronic phases of the disease [6,7]. Acute hepatitis B is generally a self-limited condition characterized by hepatocellular necrosis and in ammation.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported that the hepatitis B vaccine response is impaired in chronic HCV-infected patients, 13 15 with similar hyporesponsiveness in individuals achieving SVR following DAA treatment. 16 18 The factors contributing to suboptimal vaccine efficacy in HCV-infected individuals have not been well characterized. The host immune status plays an important role in determining the strength of the vaccine immune response.…”
Section: Introductionmentioning
confidence: 99%